2007
DOI: 10.1038/msb4100134
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale mapping of human protein–protein interactions by mass spectrometry

Abstract: Mapping protein-protein interactions is an invaluable tool for understanding protein function. Here, we report the first large-scale study of protein-protein interactions in human cells using a mass spectrometry-based approach. The study maps protein interactions for 338 bait proteins that were selected based on known or suspected disease and functional associations. Large-scale immunoprecipitation of Flag-tagged versions of these proteins followed by LC-ESI-MS/MS analysis resulted in the identification of 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
760
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 897 publications
(793 citation statements)
references
References 54 publications
27
760
1
5
Order By: Relevance
“…The differences observed in cell death can be attributed to each isoform having unique interactomes, as structural analysis of the 14-3-3 family revealed a highly variable region between α-helices 8 and 9, which determines binding specificity [42]. This concept has been validated in screens of human 14-3-3 binding partners, which revealed common and unique protein × protein interactions among the tested isoforms [43]. Further work is required to examine the interactome of each 14-3-3 isoform in beta cells.…”
Section: Discussionmentioning
confidence: 94%
“…The differences observed in cell death can be attributed to each isoform having unique interactomes, as structural analysis of the 14-3-3 family revealed a highly variable region between α-helices 8 and 9, which determines binding specificity [42]. This concept has been validated in screens of human 14-3-3 binding partners, which revealed common and unique protein × protein interactions among the tested isoforms [43]. Further work is required to examine the interactome of each 14-3-3 isoform in beta cells.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it has been shown that HNF-4α may be involved not only in glucose and lipid metabolism, but also in the DNA damage response, because HNF-4α could interact with FoxO1, 45) p53, 46) and Rad50 (a component of the MRN complex), 47) which are the targets of ATM kinase, as described above. These results emphasize the importance of HNF-4α in tumor suppression.…”
Section: Potential Role Of Hnf-4α In the Suppression Of Tumor Developmentioning
confidence: 96%
“…In vitro MT assembly assay clearly demonstrated that C53/LZAP was associated with the assembled MT but did not bind MT directly (Figure 6 proteins. Such mediators may include p35 [26] and other potential C53/LZAP-interacting protein such as Disrupted-in-Schizophrenia 1 (DISC1) protein, which is also known to bind the microtubule [27,28]. Meanwhile, a relatively large fraction of cytoplasmic C53/LZAP is associated with light membranes, such as the ER (Figure 6B and [12]), probably through its interaction with the ER protein RCAD (also known as Ufl1, NLBP and MAXER) [12,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%